P510 Hypergammaglobulinemia, hypoalbuminemia, and elevated CRP levels are predictors of a secondary loss of response to anti-TNFα therapy in IBD. (16th January 2018) - Schoenefuss, F; Hoffmann, P
Abstract: Background: We reported earlier (ECCO 2017) that low albumin and high gamma-globulin serum levels were independently associated to secondary loss of response (SLR) in patients with inflammatory bowel disease treated with anti-TNFα for the first time. We now further evaluated our cohort of patients regarding the kind of disease, the inflammatory status and changes of serum albumin levels and anti-drug antibody development under therapy. Methods: Between 2007 and 2016 we prospectively included all patients treated with either infliximab or adalimumab for IBD in our outpatient clinic. Secondary loss of response (SLR) was defined as the necessity to increase the dose or to reduce treatment intervals after an initial response to therapy. Prior to the initiation of biological treatment all patients were tested for serum-albumin, serum-gamma-globulin and CRP-levels and then the patients were followed up. Results: One hundred and two patients (52 females, 50 males; age 38.9 ± 13.7 years) were included in the study. Seventy-seven patients with Crohn's disease and 25 patients with ulcerative colitis. Of these patients 71 (69.6 %) were treated with infliximab and 31 (30.4 %) received adalimumab for the first time. Fifty-six patients (54.9 %) developed an SLR, 38 patients (37.3%) showed a sustained remission under treatment and eight patients (7.8%) were primary non-responders. Mean time to SLR was 24.8 ± 18.8 months. Hypoalbuminemia and/or hyper-gammaglobulinemia were independently associated to SLR. Patients with hypoalbuminemia had had significantly higher CRP values before anti-TNFα treatment was initiated. Patients with higher CRP values had a significantly earlier secondary loss of response but improvement of CRP within the first 6 months of therapy did not reduce the risk for SLR anymore. Although low albumin serum concentrations at the beginning of anti-TNFα therapy was associated with an earlier SLR normalisation of serum albumin under therapy did not reduce the SLR risk. Patients with hypergammaglobulinemia had a higher risk for SLR but did not show a higher rate of anti-drug antibody production compared with other patients with SLR. In our cohort patients with ulcerative colitis showed a significantly higher rate for SLR but did not differ by the means of hypalbuminemia or hypergammaglobulinemia. Conclusions: Patients with low serum albumin concentrations and higher CRP serum levels are prone to develop an earlier secondary loss of response to anti-TNFα therapy. Although these patients do not seem to develop a higher rate of anti-drug antibodies it needs to be discussed whether these patients may need a modification of therapy, e.g. a prolonged combination treatment with an immunosuppressant or at least a close meshed surveillance of drug serum concentrations.